Demographic profile of subjects currently undergoing middle meatus antrostomy for maxillary sinusitis, in a tertiary care centre of Punjab: analysis of 64 subjects - Munjal, Manish; Gupta, Ritu; Chaudhary, Anurag; Satija, Mahesh; Munjal, Shubham; Gupta, Akriti; Sawhney, Mehneet (International Journal Of Community Medicine And Public Health, 2021)
Background: The demographic profile of patients with Maxillary sinusitis undergoing surgical intervention in the state of Punjab was analyzed. The emphasis was on the age, gender and clinical presentation in this prospective study. Methods: In this prospective study 64 patients with maxillary sinusitis, were randomly selected from the Rhinology clinics of Oto-rhino-laryngology services, Dayanand Medical College and Hospital, Ludhiana in a period of one and a half years (June 2008 to December 2009). All patients were taken up for Functional endoscopic sinus surgery with middle meatus antrostomy. Results: Only 7 (10.94%) patients, with maxillary sinusitis were in the pediatric age group. 40(62.5%) were males and 24 (37.5%) females. Males outnumbered females in the ratio of 1.67:1. Clinical findings were nasal polyp in 33 (51.56%), middle meatus discharge in 10 (15.63%) and septal deviation was seen in 36 (56.25%) patients. Polypoidal mass was seen in the posterior choana in 24 (37.5%) patients followed by discharge inferior to the Eustachian tube orifice in 7 (10.94%). Recurrence of polypoidal change or frank polyposis occurred in 7 patients (10.94%). Post nasal drip persisted in 15/49 cases, while 54 (84.38%) were completely relieved of their symptoms. Recurrence was noticed more commonly in the region of ethmoid air cells. Conclusions: Patients with maxillary sinusitis were seen in the broad age range from 11 to 66 years with a male predominance. Nasal blockage rather than cheek ache was the primary complaint followed by polyp in the middle meatus and post nasal drip inferior to the Eustachian tube.